2014
DOI: 10.2341/12-417-l
|View full text |Cite
|
Sign up to set email alerts
|

Triethylene Glycol Dimethacrylate Induction of Apoptotic Proteins in Pulp Fibroblasts

Abstract: The results indicated that TEGDMA activates both the extrinsic and intrinsic apoptotic pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 25 publications
(39 reference statements)
1
8
0
Order By: Relevance
“…It is to be noted that in the presence of a high dose of TEGDMA (3 mM) no results were obtained by flow cytometry, TRAP staining, qRT-PCR, or ELISA analyses. Consistent with previous studies indicating that TEGDMA can activate apoptotic pathways 3 , 15 , this study revealed that TEGDMA caused a dose-dependent increase in apoptosis of hDPCs and cell viability has been adversely affected in the presence of high doses of TEGDMA. Therefore, it has not been possible to carry out studies on the effects of high doses of TEGDMA on odontoclastic differentiation ability of hDPCs.…”
Section: Discussionsupporting
confidence: 92%
“…It is to be noted that in the presence of a high dose of TEGDMA (3 mM) no results were obtained by flow cytometry, TRAP staining, qRT-PCR, or ELISA analyses. Consistent with previous studies indicating that TEGDMA can activate apoptotic pathways 3 , 15 , this study revealed that TEGDMA caused a dose-dependent increase in apoptosis of hDPCs and cell viability has been adversely affected in the presence of high doses of TEGDMA. Therefore, it has not been possible to carry out studies on the effects of high doses of TEGDMA on odontoclastic differentiation ability of hDPCs.…”
Section: Discussionsupporting
confidence: 92%
“…It is co-activated by TGF-β activated SMAD2 via a transactivation crosstalk with TCF4 ( 33 ). Upregulated β-catenin triggers transcriptional activation of SNAIL2-mediated EMT and proliferation signaling ( 31 , 35 ). TD-10 and TD-11 caused decrease in β-catenin implying inhibition of the canonical Wnt/β-catenin pathway yielding attenuation of the EMT as well as cell proliferation signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxicity of TD-10 has also been reported in some other studies. Batarseh et al ( 35 ) demonstrated induction of apoptotic signaling in human pulp fibroblasts by TD-10. By analyzing human apoptotic array, they found that TD-10 treated cells showed sustained upregulation of BH3 family proteins, caspase 3/8, and cytochrome c release.…”
Section: Discussionmentioning
confidence: 99%
“…Declining ATP levels and compromised redox balance as a result of mitochondrial damage are common causes of regulated cell death . Triethylene glycol dimethacrylate has previously been demonstrated to cause apoptosis through the intrinsic and extrinsic pathways . In the GO enrichment analysis, extrinsic apoptotic signaling pathways were advocated for the group treated with 2.5 mM TEGDMA.…”
Section: Discussionmentioning
confidence: 99%